Peningkatan Hasil Belajar IPS-Geografi melalui Media Gambar Diam di Kelas IV Sekolah Dasar - - Murtiningsih (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2008)
Abstract: The objective of this classroom action research is to investigate the improvement of the quality of social studies – geography learning through silent picture media. The subjects of this research were 20 male and 14 female Fourth grade students  SDN Rampal Celaket I Malang.  This research found that there was improvement of the quality of social studies – geography learning through silent picture media.